Reference in memories from perceptual and non-perceptual experiences: a non-disjunctivist account including vicarious, oneiric and fictional remembering. - Werning, Markus; Liefke, Kristina (Synthese, 2025)
The paper argues for a non-disjunctivist account of reference in episodic memory. Our account provides a uniform theory of reference for episodic memories that root in veridical and non-veridical experiences. It is independent from the particular mechanisms that subserve the respective source experiences. We reject both relationalist and intentionalist analyses of memory and build our approach on Werning and Liefke’s theory of referential parasitism and Werning’s theory of trace minimalism. The motivation for our non-disjunctivist account is the assumption that perceptual and non-perceptual memories with an episodic character share a uniform underlying causal mechanism and thus make up one and the same natural kind.